Intravital Fluorescence Videomicroscopy to Study Tumor Angiogenesis and Microcirculation - Peter Vajkoczy; Axel Ullrich; Michael D. Menger (Neoplasia: An International Journal for Oncology Research, 2000)
Angiogenesis and microcirculation play a central role in growth and metastasis of human neoplasms, and, thus, represent a major target for novel treatment strategies. Mechanistic analysis of processes involved in tumor vascularization, however, requires sophisticated in vivo experimental models and techniques. Intravital microscopy allows direct assessment of tumor angiogenesis, microcirculation and overall perfusion. Its application to the study of tumor-induced neovascularization further provides information on molecular transport and delivery, intra- and extravascular cell-to-cell and cell-tomatrix interaction, as well as tumor oxygenation and metabolism. With the recent advances in the field of bioluminescence and fluorescent reporter genes, appropriate for in vivo imaging, the intravital fluorescent microscopic approach has to be considered a powerful tool to study microvascular, cellular and molecular mechanisms of tumor growth.